Political Science in Europe at the Beginning of the 21st Century, eds. B. Krauz- Mozer, M. Kułakowska, P. Borowiec, P. Ścigaj, Jagiellonian University Press, Cracow 2015, ss. 612. - Pawłuszko, Tomasz (Przegląd Politologiczny, 2017)
Political Science in Europe at the Beginning of the 21st Century, eds. B. Krauz- Mozer, M. Kułakowska, P. Borowiec, P. Ścigaj, Jagiellonian University Press, Cracow 2015, ss. 612.